2019
DOI: 10.3390/v11030296
|View full text |Cite
|
Sign up to set email alerts
|

A Field Recombinant Strain Derived from Two Type 1 Porcine Reproductive and Respiratory Syndrome Virus (PRRSV-1) Modified Live Vaccines Shows Increased Viremia and Transmission in SPF Pigs

Abstract: In Europe, modified live vaccines (MLV) are commonly used to control porcine reproductive and respiratory syndrome virus (PRRSV) infection. However, they have been associated with safety issues such as reversion to virulence induced by mutation and/or recombination. On a French pig farm, we identified a field recombinant strain derived from two PRRSV-1 MLV (MLV1). As a result, we aimed to evaluate its clinical, virological, and transmission parameters in comparison with both parental strains. Three groups with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 36 publications
2
50
0
2
Order By: Relevance
“…An experimental study from France revealed that the Porcilis/ Unistrain recombinant virus describe above (Renson et al, 2017) seems to be more virulent than the two parent PRRSV-1 vaccine viruses (Eclercy et al, 2019). However, this study did not assess if the increased virulence of the recombinant virus reflected that the recombinant virus was adapted to swine or if it was a result of the recombination per se.…”
Section: F I G U R Ementioning
confidence: 91%
“…An experimental study from France revealed that the Porcilis/ Unistrain recombinant virus describe above (Renson et al, 2017) seems to be more virulent than the two parent PRRSV-1 vaccine viruses (Eclercy et al, 2019). However, this study did not assess if the increased virulence of the recombinant virus reflected that the recombinant virus was adapted to swine or if it was a result of the recombination per se.…”
Section: F I G U R Ementioning
confidence: 91%
“…RNA recombination has experimentally been proven by coinfections of cells or swine with two different strains of PRRSV (Liu et al, 2011;Yuan et al, 1999). During the recent epidemiological investigations, recombination has been detected between two wild-type PRRSV strains (Franzo et al, 2014;Kwon et al, 2019;Zhao et al, 2015), between wild-type PRRSV and MLV vaccine (Bian et al, 2017;Wang et al, 2019a;Zhou et al, 2018) or between MLV vaccine strains (Eclercy et al, 2019).…”
Section: Genomic Rna Recombinationmentioning
confidence: 99%
“…Aufgrund der in dieser Studie nicht erfolgten Unterscheidung zwischen Impf-und Feldviren ist auch denkbar, dass die erhöhten PCR-Nachweise in den Betriebsjahren mit Impfung von Impfviren stammten. Da bekannt ist, dass die PRRS-Viren eine hohe Mutationsrate besitzen und Virulenzgene zwischen Impfund Feldstämmen ausgetauscht werden können [32] [33], sollte eine hohe Viruszirkulation im Bestand stets vermieden werden. Nach erfolgreicher Stabilisierung sollte deshalb eine weitere Bestandsimpfung, insbesondere unter Einsatz von Lebendimpfstoff gegen PRRSV, einer kritischen Prüfung unterliegen und überlegt werden, ob andere Maßnahmen eventuell einen ähnlichen Erfolg haben können.…”
Section: Diskussionunclassified